2012
DOI: 10.1177/0884533612470145
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Chronic Liver Disease

Abstract: Osteoporosis is a common skeletal complication seen in patients with chronic liver disease. Osteoporosis is usually asymptomatic and, if untreated, can result in fractures and impaired quality of life. For this review, we performed a systematic search of the PubMed database, and all recent peer-reviewed articles regarding the prevalence, pathophysiology, diagnosis, and management of osteoporosis in chronic liver disease were included. The prevalence of osteoporosis varies between 11% and 58% in patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 84 publications
0
34
1
1
Order By: Relevance
“…Surprisingly, this study showed that loss of skeletal muscle mass before surgery in patients with HCC is associated with osteoporosis, independent of age or sex. It is known that osteoporosis is a complication commonly observed in patients with chronic liver disease regardless of cause or severity . Furthermore, it is known that metabolism of muscle and bone is regulated by some common factors such as genetic background, nutrition, lifestyle, and hormones .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, this study showed that loss of skeletal muscle mass before surgery in patients with HCC is associated with osteoporosis, independent of age or sex. It is known that osteoporosis is a complication commonly observed in patients with chronic liver disease regardless of cause or severity . Furthermore, it is known that metabolism of muscle and bone is regulated by some common factors such as genetic background, nutrition, lifestyle, and hormones .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that osteoporosis is a complication commonly observed in patients with chronic liver disease regardless of cause or severity. [36][37][38] Furthermore, it is known that metabolism of muscle and bone is regulated by some common factors such as genetic background, nutrition, lifestyle, and hormones. [39][40][41][42] For example, myokine, an endocrine cytokine or peptide released from muscle, is a potent factor related to the metabolism of both muscle and bone.…”
Section: Discussionmentioning
confidence: 99%
“…1) Liver plays a fundamental role in metabolism of vitamins D and K, parathyroid hormone (PTH) and minerals, essential regulators of bone homeostasis [1][2][3][4][5]. 2) Osteopenia/ osteoporosis (hepatic osteodystrophy) is present in 20-50% of patients with chronic liver disease [6][7][8][9][10]. 3) Osteocalcin (OC), an osteoblast-derived hormone, is recognized as a critical determinant of energy and glucose homeostasis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the adverse effects of bisphosphonates described in the literature include osteonecrosis of the jaw (75) and suppression of bone turnover with the consequent risk of atypical fractures (101). There are no specific guidelines regarding the duration of treatment in patients with CLD and ALD: In general, annual densitometric tests are recommended in CLD with high risk of accelerated bone loss, as is the case in patients with severe cholestasis, on steroid therapy, and in transplanted subjects.…”
Section: Bisphosphonatesmentioning
confidence: 99%